A Robust Control Chart for Monitoring Dispersion - Maoyuan Zhou; Wei Geng (Journal of Applied Mathematics)
Most robust control charts in the literature are for monitoring process location parameters, such as mean or median, rather than process dispersion parameters. This paper develops a new robust control chart by integrating a two-sample nonparametric test into the effective change-point model. Our proposed chart is easy in computation, convenient to use, and very powerful in detecting process dispersion shifts.